Tantangan Otoritas Jasa Keuangan Dalam Mengimplementasikan Fungsi Pengawasan Terhadap Lembaga Perasuransian - Rifa Putria Larasati; Waluyo Waluyo; Asianto Nugroho (International Forum of Researchers and Lecturers, 2025)
The phenomenon of default on insurance policy claims is quite rampant in Indonesia, for example what happened to PT Jiwasraya and AJB Bumiputera 1912 so that the implementation of the supervisory function by the Financial Services Authority is questioned. This research aims to find out how the challenges of the Financial Services Authority in implementing the supervisory function of insurance institutions. This research uses normative legal research with literature study. The results of this study indicate that the Financial Services Authority implements its supervisory function using the risk-based supervision (RBS) method and faces challenges in implementing its supervisory function, namely: limited data, human resources, and budget; the complexity of financial institutions; changes in organizational culture within the Financial Services Authority and insurance institutions; and lack of financial literacy among the public.